Designing an emotional intelligence model in reconciling emotional relationships with mediated communication skills in married women - Shayesteh Fard, Zahra; Sobhi Gharamaleki, Naser; Zargham Hajebi, Majid (Applied Family Therapy Journal (AFTJ), 2022)
Aim: Maintaining compromise in couples' relationships is the most important pillar of family foundation stability. Therefore, the present study was conducted to present a model of emotional intelligence in compromising emotional relationships mediated by communication skills in students of Hamadan University of Medical Sciences. Methods: The subjects were 410 married female students of Hamadan University of Medical Sciences in 2010-2011. (CPQ) was completed as an available sample. Data analysis was performed by path analysis using AMOS and SPSS software version 20. Results: The results showed that directly in the components of emotional intelligence, responsibility and happiness in a positive way with 99% confidence and also stress tolerance in a negative way and with 95% confidence in emotional compromise in couples. Regarding the indirect relationship between emotional intelligence components and emotional compromise mediated by communication skills, it is positive and significant at 99% confidence level. Conclusion Due to the significant role of emotional intelligence components, communication skills, therapists can discuss the level of responsibility, happiness, increased resilience to stress and communication skills training in couples in discussing and treating marital adjustment problems.